Characterisation of the pulmonary vascular response to hypoxia in mitochondrial uncoupling protein 2 deficient mice - Höres, Timm; Justus Liebig University Giessen (My University, 2013)
Hypoxic pulmonary vasoconstriction (HPV) is a specific physiological reaction of the pulmonary circulation which optimizes pulmonary gas exchange. Due to selective vaso-constriction of precapillary pulmonary vessels, systemic oxygen availability is pre-served in case of a localized reduction of ventilation or a lack of local alveolar oxygen. Additional interdependent mechanisms lead to vascular remodelling during adaptation to chronic hypoxia. Similar changes are also part of the pathogenesis of certain severe pulmonary vascular diseases. Despite intensive research, the sub-cellular and molecular nature of the mechanisms enabling HPV and vascular remodelling due to hypoxia re-main unclear. Uncoupling protein 2 (UCP-2) is a mitochondrial protein and a more re-cently identified homologue of the protein thermogenin (UCP-1). Recent studies sug-gest important interaction between UCP-2 and the signalling pathways of HPV. Against this background, the aim of this study was to investigate the role of UCP-2 in the lungs´ adaptation to acute, sustained and chronic hypoxia. Therefore important char-acteristics of HPV in wild-type (WT) and UCP-2 deficient (UCP-2 -/- ) mice were com-pared. It could be demonstrated that while acute HPV was enhanced in UCP-2 -/- mice, sustained HPV was attenuated. This difference was found to be specific for hypoxia as a vasoconstrictor stimulus. The muscularization of pulmonary vessels was increased un-der normoxic conditions in UCP-2 -/- mice and following exposure to chronic hypoxia the right ventricular systolic pressure was found elevated in UCP-2 -/- mice compared to WT mice. The results depict that ablation of UCP-2 divergently impacts the consecutive phases of HPV by a yet incompletely understood mechanism. This requires differences in the sen-sor or mediator systems of acute and sustained HPV. UCP-2 is able to directly or indi-rectly control the muscularization of pulmonary vessels under normoxic conditions and likely the pulmonary vascular tone under chronic hypoxia.

Die Hypoxische Pulmonale Vasokonstriktion (HPV) ist eine spezifische physiologische Reaktion des Lungenkreislaufes zur Optimierung des pulmonalen Gasaustausches. Durch selektive Engstellung von präkapillären Gefäßen wird die systemische Sauer-stoffversorgung im Fall lokal begrenzter Belüftungsstörung oder einer lokalen alveolä-ren Hypoxie aufrechterhalten. Zusätzliche, mit dieser Reaktion überlappende Mecha-nismen führen zum Gefäßumbau während chronischen Sauerstoffmangels. Diese strukturellen Veränderungen sind auch Bestandteil der Pathogenese einiger schwerwie-gender Lungengefäßerkrankungen. Trotz intensiver Forschung auf diesem Gebiet sind die subzellulären und molekularen Grundlagen der HPV und des Gefäßumbaues unter Hypoxie weiterhin unklar. Das Uncoupling Protein 2 (UCP-2) ist ein mitochondriales Protein, welches Homologien zu dem länger bekannten Protein Thermogenin (UCP-1) besitzt. Aktuelle Untersuchungen weisen auf wichtige Wechselbeziehungen zwischen UCP-2 und den Signalwegen der HPV hin. Davon ausgehend war das Ziel dieser Arbeit die Bedeutung von UCP-2 für die Reaktio-nen des Lungenkreislaufes auf akute, anhaltende und chronische Hypoxie zu untersu-chen. Daher wurde die Ausprägung wichtiger Merkmale der HPV von Wildtyp- (WT) und UCP-2 defizienten (UCP-2 -/- ) Mäusen verglichen. Es zeigte sich, dass die akute HPV in UCP-2 -/- Mäusen verstärkt abläuft, während die anhaltende HPV abgeschwächt ist. Dieser Unterschied war nur für eine durch Hypoxie ausgelöste Gefäßkontraktion nachweisbar. Unter Normoxie ist der Muskularisierungsgrad der pulmonalen Gefäße in den UCP-2 -/- Mäusen erhöht und nach Exposition gegenüber chronischer Hypoxie zeig-ten UCP-2 -/- , verglichen mit WT Mäusen einen erhöhten rechtsventrikulären systoli-schen Druck. Die Ergebnisse verdeutlichen, dass die Ausschaltung von UCP-2 die auf-einanderfolgenden Phasen der HPV über einen bisher nicht aufgeklärten Mechanismus in gegensätzlicher Weise beeinflusst. Voraussetzung dafür sind Unterschiede in den Sensor- oder Mediatorsystemen der akuten und anhaltenden HPV. UCP-2 reguliert unter normoxischen Bedingungen direkt oder indirekt den Muskularisierungsgrad von pul-monalen Gefäßen und wahrscheinlich auch den pulmonalen Gefäßtonus unter chroni-scher Hypoxie.
Charakterisierung der Reaktion pulmonaler Gefäße von mitochondrialen Uncoupling Protein 2 defizienten Mäusen auf Hypoxie
Keywords: UCP; Hypoxie; Pulmonal; Vasokonstriktion; Sauerstoff; UCP; hypoxia; pulmonary; vasoconstriction; oxygen; ddc:610